IDENTIFIKASI FRAKSI PROTEIN pI 8 HASIL EKSTRAKSI ASAM LIMBAH IKAN TENGGIRI SERTA STUDI POTENSINYA SEBAGAI BAHAN FORTIFIKASI MAKANAN - , META EKARISTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Identification of pI 8 protein fraction from narrow-barred Spanish mackerel waste acidic extraction and study its potential as food fortificate have been done. The research objectives were to determine nutrient composition from mackerel fish byproduct, to determine composition and essential amino acids content from precipitation of protein at pH 8, and to study its potential for food fortification. Research began with preparation of the fish waste by cutting, drying, and grinding at 50-100 mesh. Fat was eliminated by Soxhlet extraction. Fat-free sample was extracted using HCl at pH 2. Soluble protein was precipitated at pH 8 with NaOH solution. Protein fraction was washed and dried by freeze drying for 18 hours. Protein powder was hydrolyzed with HCl 6 M for 24 hours. Composition and amino acid content was analyzed by using HPLC with 14 standard amino acids. The research shows that moisture content, crude fat content, and total protein content of narrow-barred Spanish mackerel fish waste are 9.00%, 28.10%, and 29.95%, respectively. Five greatest fat composition are palmitic acid (39.17%), oleic acid (22.27%), stearic acid (11.27%), palmitoleic acid (9.67%), and tetradecanoic acid (4.98%). Protein precipitated at pH 8 is 90.55% and amino acid identified is 11.33% from total protein in mackerel fish byproduct. Essential amino acids composition found are Histidine 0.24%, Methionine 0.41%, Valine 0.50%, Phenylalanine 0.28%, Isoleucine 0.41%, Leucine 0.95%, and Lysine 1.96%. Essential amino acid score is below the standard according to FAO/WHO so the narrow-barred Spanish mackerel fish waste protein acid extracted and precipitated at pH 8 has not yet been potential for food fortification.